Role of Radiologic Technologists in Image Quality Optimization and Repeat Imaging Reduction in Diagnostic Radiology - Abbas Mohammed Abbas Alshalan; Faiz Farhan J Alenezi; Alshammari, Adel Mufadhi F; Bandar Obaydullah Amiq Alanazi; Khamis Abdullah Ayesh Al Balawi; Hajer Saleh Abdulla Alshmmari; Munawir Ayed Munawir Alshammari; Owaid Maazir A Alhzmi; Zaid Odhayb Sager Al Anazi; Alotaibi, Saber Hamoud K; et al. (International Journal of Computational and Experimental Science and Engineering, 2024)
Radiologic technologists serve as the essential frontline operators and decision-makers in diagnostic imaging, directly responsible for producing high-quality images while minimizing avoidable repeat examinations. Their role encompasses a sophisticated integration of technical expertise and patient-centered care. Through precise selection of exposure parameters, accurate patient positioning, and effective communication, they establish the foundational conditions for diagnostic accuracy. By mastering advanced imaging technology and adhering to optimized protocols, they harness tools like exposure indices and dose modulation to balance image quality with patient safety. Furthermore, their diligent execution of quality assurance tests and active participation in repeat analysis programs foster a culture of continuous improvement and radiation safety. Ultimately, the technologist’s judgment at every step—from patient assessment to image processing—is the critical determinant in achieving diagnostic efficacy, enhancing patient outcomes by reducing unnecessary radiation exposure, decreasing anxiety, and improving departmental workflow efficiency through first-time imaging success.